Archaeological Study of Islamic History in Minahasa - Marzuki, Irfanuddin Wahid (LPPM IAIN Kudus, 2020)
This article shed light on an archaeological study about the spread of Islam in the land of Minahasa of North Sulawesi Province. As the biggest ethnic group living in North Sulawesi Province, most of its people are Christians. Islam arrival in Minahasa carried by Arab traders, habaib from Hadramaut, and political prisoners (Kiai Modjo, Tuanku Imam Bondjol, Kiai Ahmad Rivai, and Tubagus Buang). As a discipline with a focus on ancient cultural heritage, archaeology works based on the material culture taking the form of artifacts, ecofacts, or features. This study enables an investigation on Islamic history in Minahasa based existing physical cultural. The archaeological study on the history of spread of Islam in Minahasa is of novelty since the previous researches of the same topic were mostly conducted through manuscript and archive study. The result of the field observation reveals that the influence of Islamic culture in Minahasa comprises of some Islamic settlements, mosques, and Islamic cemetery. The influence of Islamic culture in Minahasa has a different character between coastal and inland areas.